Design of 3D Image Visual Communication System for Automatic Reconstruction of Digital Images - Yuting Li (Advances in Multimedia)
In order to improve the visual communication effect of the 3D image visual communication system, this article combines the automatic reconstruction technology of digital images to design the 3D image visual communication system. Moreover, this article studies the shock stability of the shock capture scheme by combining entropy generation analysis, linear disturbance analysis, and numerical experiments. In addition to this, this article presents a general method that can be used to suppress numerical shock instabilities in various Godunov-type schemes. It can be seen from the experimental results that the proposed 3D image visual communication system for the automatic reconstruction of digital images has a good visual communication effect.